2022
DOI: 10.1007/s40744-022-00489-y
|View full text |Cite
|
Sign up to set email alerts
|

Content Validity of Sjögren’s Syndrome Symptom Diary and Functional Assessment of Chronic Illness Therapy-Fatigue in Patients with Sjögren’s

Abstract: Introduction: Sjo ¨gren's Syndrome Symptom Diary (SSSD) and Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) are patient-reported outcome (PRO) instruments assessing Sjo ¨gren's symptoms. Original SSSD items have demonstrated content validity, however qualitative evidence supporting the updated 'tiredness' item and two new supplementary items is lacking. Although well established and validated in other rheumatic diseases, there is no qualitative evidence sup-porting content validity of FACIT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Final scores are the sum of the responses, ranging 0–52. Higher scores indicate better quality of life 38 . OSDI is a 12-item questionnaire that assesses dry eye symptoms and their impact on daily activities 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Final scores are the sum of the responses, ranging 0–52. Higher scores indicate better quality of life 38 . OSDI is a 12-item questionnaire that assesses dry eye symptoms and their impact on daily activities 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Functional Assessment of Chronic Illness Therapy (Fatigue) (FACIT-F): This was developed in 1997 to measure fatigue in oncology. However, it has subsequently been used to assess chronic illness, and more recently, Natasha Griffiths et al have demonstrated the content validity of this questionnaire in pSS [9].…”
mentioning
confidence: 99%